Estudo dos efeitos da radiação ultravioleta C e TFD em células de Saccharomyces boulardii e Candida albicans - Vargas, Karina Colasso (2011)
The study of some effecs of ultraviolet C (UVC) and photodynamic therapy (PDT) in S. boulardii and C. albicans cells was performed by exposing the cells to different radiation intensities, and was computed based on the exposure time and power sources used. The exposure to UV-C was performed after the inoculation of microorganisms in YEPD agar and immediately exposed to UV-C rays at distance of 35 cm from the source for lengths of time ranging from 40s to 5s for S. boulardii and from 10s to 60s for C. albicans. The experiments were performed in triplicate, once for checking the cell’s sensitivity by radiation and once to test the occurrence of photoreactivation after irradiation with UV-C. The cells considered mutants, isolated in another experiment, were submitted to biochemical tests to assess changes in their metabolism, and, later, microscopy to assess morphological changes. The experiments with PDT were done by exposing the microorganisms to the photosensitizing agents and later to the LED bulb for lengths of time ranging from 3 min to 12 min. The results show that UV-C is effective in reducing the population of microorganisms. The biochemical tests also showed changes in the metabolism of the S. boulardii such as a loss in the ability to assimilate sugars and nitrogen sources. The morphological changes were cell elongation and reduction of the colony size. PDT, in turn, showed no antimicrobial action with this methodology. There was only an apparent recuperation of cells that were exposed to toxic substances used in its photosensitization. Our conclusion is that the pathogenic yeast C. albicans is more resistant to UV-C rays compared with the S. boulardii because it needs 60 seconds of exposure to UV-C against 40 seconds for a decimal reduction of S. boulardii. The methodology used for PDT in this study did not cause population reduction in the studied cells.